Market Dependency and Household Food Consumption in East Java, Indonesia - Erna Maria Lokollo (Jurnal Agro Ekonomi, 2001)
IndonesianTujuan utama penelitian ini adalah untuk melihat perbedaan diantara konsumen di daerah pedesaan dan perkotaan dalam mengkonsumsi bahan makanan utama, dan terutama menelusuri seberapa jauh konsumsi di masing-masing lokasi (desa dan kota) tergantung pada uang tunai dan pasar (cash or market dependency) untuk pemenuhan konsumsi bahan makanan tersebut. Data dianalisis dari SUSENAS 1993, BPS, Provinsi Jawa Timur. Hasil penelitian menunjukkan bahwa ketergantungan akan uang tunai dan pasar berhubungan erat dengan jumlah konsumsi bahan makanan yang akan dibeli. Terdapat perbedaan nyata antara konsumen di daerah pedesaan dan perkotaaan, dimana konsumen di pedesaan memiliki angka ketergantungan uang tunai dan pasar yang lebih rendah daripada konsumen di perkotaan. Asumsi lama dan klasik yang menyatakan bahwa penduduk di pedesaan kebanyakan adalah petani subsisten (yang dapat memproduksi untuk dikonsumsi sendiri) sudah tidak berlaku lagi. Walaupun demikian masih didapati bahwa seringkali rumahtangga di pedesaan menjual bahan makanan berkualitas lebih baik yang diproduksinya, sehingga uang hasil penjualan tersebut dapat digunakan untuk membeli kualitas yang lebih rendah, yang berarti memaksimumkan konsumsi dari segi kuantitas. Hasil penelitian ini menyiratkan pentingnya pengambil keputusan menyadari perbedaan antara penduduk desa dan kota tersebut.  Studi semacam ini apabila ditunjang oleh studi perilaku marketed dan marketable surplus dapat membantu pembuat kebijaksanaan di bidang pengadaan dan distribusi pangan. Studi ini juga membantu memperjelas adanya perilaku ketergantungan pada uang tunai dan pasar yang berbeda pada rumahtangga di daerah desa dan perkotaan.EnglishThe general purpose of this study was to examine the differences between rural and urban consumers in how they acquire the food they consume and, in particular, to determine how much consumers in each location depend on cash for procuring the food they consume. The quantity of food purchased was modeled as a function of cash dependency, household income, household size and prices. Data were taken from the 1993 Survey Sosial Ekonomi Nasional (SUSENAS) in East Java, conducted by the Biro Pusat Statistik - BPS (Central Bureau of statistics), Indonesia. The results of this study indicate that the cash dependency for all food categories examined was significantly related to the quantities purchased of the foods (cereals, tubers, vegetables, fruits). Significant differences in cash dependency were also found between rural and urban consumers, with rural consumers having lower food cash dependency ratios than urban consumers. Perhaps the most surprising discovery was that the vast majority of rural consumers also depend on cash for acquiring food. The old assumption that mostly people in the rural areas in Indonesia are subsistence farmers (consume what they own produce) is no longer hold. The data from the survey shows that there are less and less subsistence farming exists in the area (East Java). The maintenance of subsistence farming may, indeed, be of strategic importance for the satisfaction of basic needs and the survival of rural households. When production from own sources is inadequate to meet the consumption needs, the households concerned may sell superior food (i.e., superior cereals or superior varieties) they produce, so as to maximize their purchasing power with which they can purchase inferior cereals and meet their own needs - thus maximizing their consumption at least in quantity. This study stresses the importance of using household consumption data in the making of public policy (food policy). They are important in that the implementation of policy will affect large number of people. lt even will affect rural and urban consumers differently. This study combined with a study of behavior of marketed and marketable surplus can be significant help in designing a system of procurement and public distribution. This study also can help in understanding the behavior of purchase of food by farmers in different areas.